Seasonal use case for the RTS, S/AS01 malaria vaccine: a mathematical modelling study. Issue 12 (December 2022) - Thompson, Hayley A; Hogan, Alexandra B; Walker, Patrick G T; Winskill, Peter; Zongo, Issaka; Sagara, Issaka; Tinto, Halidou; Ouedraogo, Jean-Bosco; Dicko, Alassane; Chandramohan, Daniel; Greenwood, Brian; Cairns, Matt; et al.
Summary: Background: A 2021 clinical trial of seasonal RTS, S/AS01E (RTS, S) vaccination showed that vaccination was non-inferior to seasonal malaria chemoprevention (SMC) in preventing clinical malaria. The combination of these two interventions provided significant additional protection against clinical and severe malaria outcomes. Projections of the effect of this novel approach to RTS, S vaccination in seasonal transmission settings for extended timeframes and across a range of epidemiological settings are needed to inform policy recommendations. Methods: We used a mathematical, individual-based model of malaria transmission that was fitted to data on the relationship between entomological inoculation rate and parasite prevalence, clinical disease, severe disease, and deaths from multiple sites across Africa. The model was validated with results from a phase 3b trial assessing the effect of SV-RTS, S in Mali and Burkina Faso. We developed three intervention efficacy models with varying degrees and durations of protection for our population-level modelling analysis to assess the potential effect of an RTS, S vaccination schedule based on age (doses were delivered to children aged 6 months, 7·5 months, and 9 months for the first three doses, and at 27 months of age for the fourth dose) or season (children aged 5–17 months at the time of first vaccination received the first three doses in the 3 months preceding the transmission season, with any subsequent doses up to five doses delivered annually) in seasonal transmission settings both in the absence and presence of SMC with sulfadoxine–pyrimethamine plus amodiaquine. This is modelled as a full therapeutic course delivered every month for four or five months of the peak in transmission season. Estimates of cases and deaths averted in a population of 100 000 children aged 0–5 years were calculated over a 15-year time period for a range of levels of malaria transmission intensity ( Plasmodium falciparum parasite prevalence in children aged 2–10 years between 10% and 65%) and over two west Africa seasonality archetypes. Findings: Seasonally targeting RTS, S resulted in greater absolute reductions in malaria cases and deaths compared with an age-based strategy, averting an additional 14 000–47 000 cases per 100 000 children aged 5 years and younger over 15 years, dependent on seasonality and transmission intensity. We predicted that adding seasonally targeted RTS, S to SMC would reduce clinical incidence by up to an additional 42 000–67 000 cases per 100 000 children aged 5 years and younger over 15 years compared with SMC alone. Transmission season duration was a key determinant of intervention effect, with the advantage of adding RTS, S to SMC predicted to be smaller with shorter transmission seasons. Interpretation: RTS, S vaccination in seasonal settings could be a valuable additional tool to existing interventions, with seasonal delivery maximising the effect relative to an age-based approach. Decisions surrounding deployment strategies of RTS, S in such settings will need to consider the local and regional variations in seasonality, current rates of other interventions, and potential achievable RTS, S coverage. Funding: UK Medical Research Council, UK Foreign Commonwealth & Development Office, The Wellcome Trust, and The Royal society.